The Torch Bearer - Marquis, Reina Melcher, 1881- (Salt Lake City, UT : Project Gutenberg, 2010)
"The Torch Bearer" by Reina Melcher Marquis is a novel written in the early 20th century. The story centers around Peter Burnett, a young schoolmaster, and his interactions with the charming but peculiar Sheila, an orphan girl he teaches at a girls$1 (Bseminary run by Mrs. Caldwell. The book explores themes of growth, mentorship, and artistic aspiration in the delicate framework of Southern society in Shadyville, Kentucky. The opening of the narrative introduces Peter Burnett as he enjoys the freedom of a weekend away from teaching, offering a glimpse into his character$1 (Bintelligent yet somewhat indifferent to societal expectations. As he strolls through Shadyville, Peter encounters Mrs. Caldwell, who brings his attention to Sheila, her beloved granddaughter. Their conversation reveals Sheila's extraordinary intellect and imaginative nature, reminiscent of a budding poet, which Mrs. Caldwell is worried may isolate her from the world. The chapter deftly establishes Peter$1 (Bs role as a mentor to Sheila, hinting at his own internal struggles and desires for a more engaging life, setting the stage for the relationships and conflicts that will unfold throughout the novel. (This is an automatically generated summary.)s
Release date is 2010-05-16
Produced by Al Haines
Keywords: Married women -- Fiction; Women authors -- Fiction; Mothers -- Fiction